Poll Tax - TGWU pamphlet, 1989 (London, 1989)
1989 1980-95 "Poll Tax - TGWU pamphlet, 1989" [BW0088], 1989, Trades Union Congress The Community Charge was a poll tax to fund local government, instituted by the Conservative government in 1989. It replaced the rates that were based on the notional rental value of a house. This pamphlet in the Transport and General Workers' Union 'Ammo' series urges union members to campaign against it.